Estratégias para Planejamento e Recomposição em Redes de Telecomunicações - Barreto, Maurício Beraldin (Universidade do Vale do Rio dos Sinos, 2011)
The growth of traffic on telecommunications networks for broadband services, fixed and mobile telephony has demanded efforts in planning and study the restoration of the network, especially transport networks, making the high level of complexity in developing projects that involve networks. The interconnection complexity increases with the restrictions imposed by the capacity of investment and operating costs in obtaining the optimal solution for the best network topology. To resolve issues of planning and rebuilding of the telecommunication networks is necessary to use computational resources, since problems involving networks of this nature have the feature set of combinatorial optimization problems, considered difficult. With the objective to plan and carry out studies on the recomposition of the telecommunications network, in this work the strategy for use as heuristic genetic algorithm and Dijkstra, as well as the concept of fictitious network modeling and computational solution to obtain the solution great on the network topology, enabling preliminary analysis of traffic on the proposed topology where there incidence of failures.
Keywords: Planejamento de redes de telecomunicações; Redes ASON; Simulação de múltiplas falhas em rede de transporte; Algoritmo de Dijkstra; Algoritmo Genético; Planning of telecommunication network; ASON networks; Simulation of multiple failures in the transport network; Dijkstra's algorithm; Genetic algorithm; Algoritmo genético; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação